The Influence of Habitat Management on Pod Borer Conopomorpha cramerella and Mirid Helopeltis antonii Attack on Cocoa - Ardiyanti Purwaningsih; Gatot Mudjiono; Sri Karindah (Jurnal Tanaman Industri dan Penyegar, 2014)
Habitat management of cocoa cultivation must be carried out to improve the fertility of soil, increase the biodiversity and the plant’s health. The objective of this study was to elucidate the effect of habitat management on the cocoa pod borer Conophomorpha cramerella and cocoa mirid Helopeltis antonii attack. The research was conducted from October 2013 to April 2014 in Sumbermanjing Wetan District, Malang Regency, East Java. The research was compared cocoa plantation with habitat management and the conventionally managed cocoa plantation as a control. Habitat manipulation techniques used in this research were providing ditch and worm biopores, applying organic matter and compost tea drip irrigation. There were 24 sub blocks for each plot and 4 plants per sub block. The results showed that the habitat management was capable to increase the number of cocoa pods, stimulate an increasing in the diversity of insects, particularly the number of natural enemies, and decrease the percentage and intensity of C. cramerella and H. antonii attack.